Effect of perioperative intravenous lidocaine on the incidence of short‐term cognitive function after noncardiac surgery: A meta‐analysis based on randomized controlled trials. Issue 12 (12th October 2020) - Huang, Xiao; Sun, Yuan; Lin, Dandan; Wei, Changwei; Wu, Anshi
Abstract: Objectives: Postoperative cognitive dysfunction is a debilitating postoperative complication. The perioperative neuroprotective effect of lidocaine has conflicting results. Methods: In this qualitative review of randomized controlled clinical trials on the perioperative use of lidocaine, we report the effects of intravenous lidocaine on brain function after noncardiac surgery. Studies were identified from PubMed, MEDLINE, and Cochrane Central Register. Results: Of the 453 retrieved studies, 4 randomized trials were included. No significant association between the use of lidocaine postoperative cognitive states was found (risk ratio 0.67; 95% CI −0.02 to 1.36; I 2 89%; p  = .06). Conclusions: Current evidence cannot suggest that perioperative intravenous use of lidocaine has pharmacological brain neuroprotection after noncardiac surgery. All the included studies were small‐scale research, and the total number of participants was small; the results should be interpreted with caution. Abstract : Current evidence cannot suggest that perioperative use of lidocaine has pharmacological brain neuroprotection after noncardiac surgery. All the included studies were small‐scale research, and the total number of participants was small; the results should be interpreted with caution.